A Retrospective Review of an Epidural Blood Patch Database: The Incidence of Epidural Blood Patch Associated With Obstetric Neuraxial Anesthetic Techniques and the Effect of Blood Volume on Efficacy. Issue 4 (December 2017) - Booth, J.L.; Pan, P.H.; Thomas, J.A.; Harris, L.C.; D'Angelo, R.
Abstract : ( Int J Obstet Anesth 2017;29:10–17) Postdural puncture headache (PDPH) is one of the most common obstetric anesthesia complications. One estimate of the proportion of parturients suffering a PDPH is 1.5%. However, among obstetric patients who have experienced a dural puncture with an epidural needle (epidural wet tap) rates of PDPH have been reported as high as 81%. While an epidural blood patch (EBP) is a standard treatment for PDPH, with success rates from different studies varying between 61% and 98%, there is no general consensus regarding the optimal volume of blood to be used for the procedure.